PROBLEMATIKA LINGKUNGAN BAHASA ARAB DI PONDOK PESANTREN RAUDLATUL MALIKIYAH KETAPANG KOTA PROBOLINGGO - Auwalinna Maulita, Arfa An Nisa’a (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
This research was motivated by the problem of the Arabic language environment in the Raudlatul Malikiyah Islamic Boarding School Ketapang Probolinggo City. The purpose of this study is to find out and analyze problems and solutions in the creation of an Arabic language environment at the Raudlatul Malikiyah Islamic Boarding School Ketapang Probolinggo City. The method used by researchers is qualitative method and data collection by: observation method, interview and documentation. The results showed that the creation of an Arabic language environment has not run optimally. This is because there are several obstacles that exist in the field such as the decline in the enthusiasm for learning students in Arabic in addition, the confidence to express Arabic sentences is very decreased, there are still some Ustadzah (Teacher) councils who are not in the field of Arabic have not used Arabic as the language of communication applied in pesantren, and many musrifah often use languages other than Arabic.